Designing interactions. - Moggridge, Bill, ....- (Cambridge : MIT, 2007)
A pioneer in interaction design tells the stories of designers who changed the way people use everyday things in the digital era, interviewing the founders of Google, the creator of The Sims, the inventors and developers of the mouse and the desktop, and many others.
Keywords: Industrieel ontwerpen